2015
DOI: 10.1002/anie.201504248
|View full text |Cite
|
Sign up to set email alerts
|

A Hollow Foldecture with Truncated Trigonal Bipyramid Shape from the Self‐Assembly of an 11‐Helical Foldamer

Abstract: The creation of self-assembling microscale architectures that possess new and useful physical properties remains a significant challenge. Herein we report that an 11-helical foldamer self-assembles in a controlled manner to form a series of 3D foldectures with unusual three-fold symmetrical shapes that are distinct from those generated from 12-helical foldamers. The foldamer packing motif was revealed by powder X-ray diffraction technique, and provides an important link between the molecular-level symmetry and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…However, peptide scaffolds are represented as elegant motifs to construct self‐assembled functional materials. [38–63] Hybrid peptides constructed by conventional and un‐conventional amino acids tend to form well‐organized supramolecular structures and which are used as functional materials . Over the past few years, we have explored various applications of low molecular weight linear peptides, which show remarkable self‐assembled nano‐structures under certain physical conditions …”
Section: Introductionmentioning
confidence: 99%
“…However, peptide scaffolds are represented as elegant motifs to construct self‐assembled functional materials. [38–63] Hybrid peptides constructed by conventional and un‐conventional amino acids tend to form well‐organized supramolecular structures and which are used as functional materials . Over the past few years, we have explored various applications of low molecular weight linear peptides, which show remarkable self‐assembled nano‐structures under certain physical conditions …”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that the structural diversity of foldectures encompasses highly exotic 3D morphologies, such as molar teeth and hollow bipyramids . To the best of our knowledge, these are exceptionally unique examples of anisotropic 3D shapes that have not been observed in previous studies of other self‐assembled organic materials.…”
Section: Introductionmentioning
confidence: 69%
“…Mixed α-β Foldamers Beyond the foldectures based on 12-helices of β-foldamers already reported in Section 2.3, Lee's group also extensively studied the aqueous self-assembly in solid shapes of surfactant-containing solutions of 1:1 alternating α-β foldamers showing the repetition of the Aib-trans-ACPC sequence, as shown in Figure 24a [261][262][263][264][265]. In all of these studies, the exact packing mode could be ascertained by an intelligent use of high-resolution powder X-ray diffraction (PXRD), whereas the morphologies of self-assembled nanostructures were observed by SEM and additional information could be obtained by applying various physico-chemical analyses, such as differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and FT-IR.…”
Section: Aliphatic Foldamers With Heterogeneous Backbones In Aqueous Environmentmentioning
confidence: 99%
“…Adding an Aib residue at the C-terminus, thus using the heptamer Boc-(Aib-ACPC) 3 -Aib-OBn, depicted by R 2 = Aib-OBn in Figure 24a, and exploiting again the differential solvation in water or aqueous P123 solutions at increasing concentrations (8, 24, 40, and 48 g L −1 ) to drive the directional growth, it was possible to synthesize amazing self-assembled shapes with the same molecular packing motif [262]. In particular, the tripod (F 0 ) morphology was obtained from distilled water, while the morphologies from F 1 to F 4 , which were all based on a trigonal bipyramid, formed in 8 g L −1 (caudate trigonal bipyramid), 24 g L −1 (trigonal bipyramid), 40 g L −1 (truncated trigonal bipyramid), and 48 g L −1 (truncated trigonal bipyramid with caved face) solutions of P123, respectively, as shown in Figure 24c.…”
Section: Aliphatic Foldamers With Heterogeneous Backbones In Aqueous Environmentmentioning
confidence: 99%